Gold(I)-catalyzed cycloisomerization of 3-alkoxyl-1,6-diynes: a facile access to bicyclo[2.2.1]hept-5-en-2-ones - Hu, Chao; Wang, Tao; Rudolph, Matthias; Oeser, Thomas; Asiri, Abdullah M.; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2020)
A novel gold-catalyzed cycloisomerization of 1,6-diynes was achieved, providing an atom-economic approach to a diverse set of bicyclo[2.2.1]hept-5-en-2-ones in moderate to good yields. With unsymmetrical starting materials with two different internal alkynyl substituents, to some extent, the regioselectivity could be controlled by both electronic and steric factors. This unprecedented reactivity pattern may inspire new and unconventional strategies for the preparation of bridged ring systems.